Coping with Forest and Land Fire Regulatory Challenges in Indonesia: an Assessment to the Regulatory Enforcement - Isna , Fatimah (Journal of Vasyl Stefanyk Precarpathian National University, 2018)
The uncontrolled expansion of plantation activities within peatland areas is one of the major trigger causing forest and/or land fire (Fire) in Indonesia. To deal with such problems including other influencing variables such as land use management, Indonesian law provides various options of regulatory instrument. The law indicates strong message that the Fire must be stopped, reflected through stipulations on regulatory instruments including command and control type of regulation (direct regulation) and alternative approaches to hold compliance. After exacerbate Fire in 2015, many protests from the people, neighborhood countries and broader international parties encouraged Indonesian government to be more active in conducting regulatory enforcement of some regulatory instruments. Some of the examples are the imposed administrative sanction and lawsuit against companies within 2015 to 2017. However, the regulatory enforcement has not been assessed as to whether it has obtained significant improvement to stop Fire. This paper attempt to assess whether regulatory enforcement on selected Fire cases has met the regulatory objective particularly to stop the Fire. This research finds that output of the applied enforcement for violation on Fire provisions remains incoherent with the regulatory objective while the strategy of enforcement is not well-systemized.